Barriers to social reconstruction of communities in the aftermath of organized violence - Ajduković, Dean (2006)
War or massive terrorist attacks have distinct characteristics that disrupt social patterns, challenge the existing social institutions, may lead to shift in social structure, question the social norms and value systems, and destabilize communities in other ways. Likewise, the social milieu in which lives of survivors of armed conflicts are embedded has important consequences for individual and community recovery. Better understanding of interpersonal, intra- and inter-group processes can help us design interventions that may facilitate recovery from massive suffering in a war. During war or terrorist attacks massive pain and trauma is inflicted which is intentional, meant to hurt and destroy people, target particular groups and individuals in order to send a message to community members and other communities. Everyday people have profound need to understand why they have suffered. This search for meaning is extremely difficult and opens space for distorted perceptions, rationalizations and manipulation. Processes of in-group and out-group bias, stereotypes turning into prejudice and discrimination, between-group distrust flourish at times of massive violence and after it. People who have been exposed to such events also feel that they have suffered gross injustice and that their basic human rights have been violated. They want to see judicial trials against the individuals they see as perpetrators of human rights both within the own community and outside of it, which indicates deepness of psychological wounds. Our studies clearly identified interpersonal processes that lead to loss of mutual trust, disruption of norms and decreasing quality and efficiency in close social transactions. The task of effective community-based interventions is to help facilitate psychosocial reconstruction of the communities, decrease social tensions among groups that have been involved in a conflict, provide treatment for the most traumatized individuals and work towards re-connecting community members. The key process that may be conductive to such recovery at the community level is the social reconstruction. We see individual recovery from violence and community social reconstruction as two parallel, interdependent and non-linear processes.
Projekt MZOS
ENG